2012
DOI: 10.1002/ejoc.201200207
|View full text |Cite
|
Sign up to set email alerts
|

Total Syntheses of the Gregatins A–D and Aspertetronin A: Structure Revisions of These Compounds and of Aspertetronin B, Together with Plausible Structure Revisions of Gregatin E, Cyclogregatin, Graminin A, the Penicilliols A and B, and the Huaspenones A and B

Abstract: Comprehensive comparisons of 1H and 13C NMR chemical shift values in the furanone cores a, b, and c provide plausible support for a reassessment of the furanone nuclei of the title compounds from b to c. Total syntheses via enantiomerically pure lactic esters were based on the Seebach–Fráter “self‐reproduction of stereocenters” methodology. Attachment of the hexadienyl side‐chain in a trans,trans‐selective manner was achieved by addition of the Seebach–Fráter enolate to trans‐hex‐4‐en‐1‐al rather than to trans… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
49
1

Year Published

2013
2013
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 33 publications
(52 citation statements)
references
References 59 publications
1
49
1
Order By: Relevance
“…However, the tertiary carbon for C3 in compound 1 was converted to be a quaternary carbon in compound 5 according to the 13 CNMR spectrum and DEPT 135 spectrum, implying the existence of a substituent group at C3 in compound 5 . Moreover, comparing the 13 C‐NMR spectral data of 5 with those of a reference compound, gregatin B, we found that the carbon signals of compound 5 in the C2, C3, C13, and C14 were almost identical to those of gregatin B. Hence, the C‐3 was undoubtedly substituted by a carboxylic acid unit on the basis of the previously mentioned evidence.…”
Section: Resultsmentioning
confidence: 54%
“…However, the tertiary carbon for C3 in compound 1 was converted to be a quaternary carbon in compound 5 according to the 13 CNMR spectrum and DEPT 135 spectrum, implying the existence of a substituent group at C3 in compound 5 . Moreover, comparing the 13 C‐NMR spectral data of 5 with those of a reference compound, gregatin B, we found that the carbon signals of compound 5 in the C2, C3, C13, and C14 were almost identical to those of gregatin B. Hence, the C‐3 was undoubtedly substituted by a carboxylic acid unit on the basis of the previously mentioned evidence.…”
Section: Resultsmentioning
confidence: 54%
“…Comparison of the 1 H and 13 C NMR data of the metabolite 3 , [α] D 25 +168, with those reported for synthetic cis -gregatin B [11] suggested that they are identical with each other. The absolute configuration at the only chiral center (C-5) in synthetic 3 was established as R based on the absolute configuration of the starting materials used for its synthesis, but its [α] D value has not been determined due to the lack of sufficient material [11].…”
mentioning
confidence: 85%
“…Despite its simplicity, the central core of these metabolites has undergone several structural revisions over the past three decades. The core structure, 3-acyl-4-methoxyfuran-2( 3H )-one, the first proposed for these metabolites [8,9], was later revised to 4-acyl-3-methoxyfuran-3( 2H )-one [10], and finally to the currently accepted 4-(methoxycarbonyl)furan-3( 2H )-one [11]. Several fungal-derived furanones have been reported to have phytotoxic [12], antibacterial and antifungal activities [9] and implicated as the causal agents of stripe disease of wheat [12] and brown stem rot of adzuki beans [9].…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…9 Herein, we continued our chemical investigation on the three cytotoxic fractions G, I and L (which were active against the A549 cells with IC 50 values of 13.36, 23.63 and 25.28 mg mL À1 , respectively). Six new metabolites (1-5 and 10), together with nine known metabolites including four aromatic polyketides (6)(7)(8)(9) and ve perylenequinones (11)(12)(13)(14)(15), were obtained ( Fig. 1).…”
Section: Introductionmentioning
confidence: 99%